Biomarkers for Overweight in Adult-Onset Asthma - Tashiro, Hiroki (J Asthma Allergy, 2020)
PURPOSE: Overweight and obesity are associated with one of the severe phenotypes of asthma, with an increased rate of exacerbations, low level of lung function, and reduced response to corticosteroid therapy. The present study focused on identifying useful biomarkers of severity in overweight patients with adult-onset asthma using real-world data. PATIENTS AND METHODS: A total of 56 patients with adult-onset asthma who visited Saga University Hospital between 2018 and 2019 were retrospectively reviewed. Overweight was defined as a body mass index (BMI) greater than 25 kg/m(2). Blood eosinophils, cytokines, and chemokines were compared between non-overweight asthma and overweight asthma patients. RESULTS: Overweight asthma patients had a higher annual exacerbation rate, lower pulmonary function even when treated frequently with high-dose inhaled corticosteroids, and a significantly lower percentage of eosinophils and lower eosinophil count compared to non-overweight asthma patients (p<0.01, p=0.03). Moreover, the percentage of eosinophils was significantly negatively correlated with BMI (ρ=−0.38, p<0.01) (Figure 1). On serum cytokine and chemokine analyses, the overweight asthma group included significantly more patients with a lower level of tissue growth factor α (TGF-α) (1.1 pg/mL) and higher levels of hsIL-6 (2.5 pg/mL), RANTES/CCL5 (298.5 pg/mL), and vascular endothelial growth factor A (VEGF-A) (63.7 pg/mL), than the non-overweight asthma group (p=0.02, p<0.01, p=0.02, p=0.01, respectively). CONCLUSION: The present study showed that overweight patients with adult-onset asthma were characterized by a higher rate of annual exacerbations and worse lung function despite treatment with high-dose inhaled corticosteroids and lower blood eosinophil counts than non-overweight patients with asthma. On blood cytokine and chemokine analyses, a low level of TGF-α and high levels of hsIL-6, RANTES/CCL5, and VEGF-A might be biomarkers reflecting the pathophysiology in overweight patients with asthma.